Senam Osteoarthritis Bersama Untuk Menjaga Kebugaran Fisik dalam Rangka WPTD di SMK 7 Semarang - Lilik Sigit Wibisono; Fitratun Najizah; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti; Eriga Yessyra Syafitri (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Geriatrics is a branch of gerontology that studies the level of health in the elderly from various aspects, including: promotive, preventive, curative and rehabilitative which includes physical, mental and social health. In principle, geriatrics strives for a happy and useful old age. Throughout the world today, the number of elderly people is estimated to be more than 629 million people, and in 2025 it is projected that the number of elderly people will reach 1.2 billion. Indonesia is a country that has a fairly high number of elderly people. In 2010 the number of elderly aged 65 years and over was 11 million, and it is projected that in 2020 the number of elderly will increase by 7.2%. Even the United States Census Bureau estimates that Indonesia will experience the largest increase in elderly citizens in the world in 2025, namely 414%. The increasing number of elderly will affect the welfare of the elderly (Ministry of Welfare of the Republic of Indonesia. 2012). The increase in the elderly population is of course accompanied by the risk of various degenerative diseases such as diabetes mellitus, coronary heart disease, osteoarthritis, neuromuscular disease and lung disease. Around 50-80% of elderly people aged more than 65 years will experience more than one chronic disease. This is related to the fact that the older you get, the more health problems you experience. One way to improve the quality of life for the elderly is to do physical exercise. Physical exercise can maintain or improve flexibility, cardiopulmonary endurance, agility, strength and balance. Several studies show that physical exercise has a consistent effect in reducing the risk of falls in healthy older adults. Kuptniratsaikul's research in 2009-2010 showed that simple balance exercises carried out by elderly people with a history of falls could reduce the incidence of falls in the elderly and significantly improve body balance. A 2017 Cuevas meta-analysis study showed that balance training programs showed the greatest effect in reducing the risk of falls in the elderly. For elderly people who are not yet able to do balance exercises independently, they need professional assistance